Effective fabrication of zinc-oxide (ZnO) nanoparticles using Achyranthes aspera leaf extract and their potent biological activities against the bacterial poultry pathogens. (12th March 2021) - Saeed, Shagufta; Nawaz, Sadia; Nisar, Aneesa; Mehmood, Tahir; Tayyab, Muhammed; Nawaz, Muhammad; Firyal, Sehrish; Bilal, Muhammad; Mohyuddin, Ayesha; Ullah, Azmat
Abstract: Nanotechnology is one of the most significant area of research worldwide because of its tremendous applications linked to the high surface area to volume ratio, improved pharmacokinetic profile and targeted drug delivery. In the current study, zinc oxide nanoparticles (ZnO NPs) were synthesized from Achyranthes aspera leaf extract, characterized by UV-visible spectroscopy, XRD, SEM, FTIR, AFM and evaluated for antibacterial efficacy against poultry pathogenic bacterial strains. UV-visible absorption peak was found at 370 nm. XRD showed hexagonal wurtzite structure of ZnO NPs while SEM results indicated an average size less than 100 nm with a minimum and maximum size of 28.63 and 61.42 nm, respectively. Further analysis of synthesized nanoparticles by FTIR showed stretching frequency at 3393.14 cm −1, 2830.99 cm −1, 2285.23 cm −1, and 2108.78 cm −1 . The antibacterial activity of synthesized nanoparticles was investigated against common poultry pathogens Salmonella gallinarum and Salmonella enteritidis by the agar well diffusion method. The zone of inhibition with a diameter of 31 mm was observed against S. enteritidis and 30 mm against S. gallinarum that was greater than the antibiotic (tetracycline) used. The minimum inhibitory concentration (MIC) was 0.195 and 0.390 mg ml −1 for different bacterial strains. Characterization with different techniques showed a uniform and stable synthesis of ZnO NPs. Furthermore, the findings confirm the higher antibacterial activity of nanoconjugate in comparison to leaf extract and pure drug against pathogenic bacteria.